Tinjauan Penerapan Ketentuan Perpajakan UMKM Berdasarkan PP 55 Tahun 2022 di Kota Batam - Prilian Muhammad Fajar; Budiasih Widiastuti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2026)
Taxes are a primary source of government revenue and play a crucial role in supporting development and public welfare. Indonesia implements a self-assessment system that requires taxpayers to be aware of and comply with their tax obligations independently. This study aims to determine the level of knowledge and understanding of MSMEs in the South Batam Pratama Tax Office (KPP Pratama) working area regarding MSME tax policies, specifically those stipulated in Government Regulation Number 55 of 2022, and their impact on taxpayer compliance. The research method used was a qualitative approach with primary and secondary data through interviews, literature review, and analysis of tax data from the South Batam Pratama Tax Office using data triangulation techniques. The results indicate that most MSMEs still have limited knowledge and understanding of tax obligations and the latest policies. Lack of outreach and access to information are the main factors contributing to this low level of understanding. The implementation of Government Regulation No. 55 of 2022 has resulted in a decrease in MSME income tax payments and the number of taxpayers paying and reporting taxes, although the turnover limit incentive is considered to encourage tax awareness and compliance among MSMEs.